2017
DOI: 10.1016/j.apjtm.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Production, characterization and biological activities of acidic exopolysaccharide from marine Bacillus amyloliquefaciens 3MS 2017

Abstract: BAEPS has anti-tumor activity with a good margin of safety. The anti-tumor activity of BAEPS may be due to its content from sulfated groups and uronic acids and they have antioxidant and anti-inflammatory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
4
25
0
Order By: Relevance
“…The IC 50 value of Graesiella EPSs was estimated to be 0.22 g L −1 , a value lower than the IC 50 of L-ascorbic acid which was 0.53 g L −1 . Graesiella EPSs showed a significant (p < 0.05) superoxide radical scavenging ability which has already been reported for bacterial EPSs (El-Newary et al 2017). Previous reports on the scavenging capacity of chlorophyte EPSs have shown the possibility of sulfate content being correlated with the potent activity (Ghasemi et al 2007;Raposo et al 2014).…”
Section: Radical Scavenging Abilitysupporting
confidence: 75%
“…The IC 50 value of Graesiella EPSs was estimated to be 0.22 g L −1 , a value lower than the IC 50 of L-ascorbic acid which was 0.53 g L −1 . Graesiella EPSs showed a significant (p < 0.05) superoxide radical scavenging ability which has already been reported for bacterial EPSs (El-Newary et al 2017). Previous reports on the scavenging capacity of chlorophyte EPSs have shown the possibility of sulfate content being correlated with the potent activity (Ghasemi et al 2007;Raposo et al 2014).…”
Section: Radical Scavenging Abilitysupporting
confidence: 75%
“…Molecular weight of EPS. The molecular weight of the EPS from strain GSBa-1 was determined to be 54 kDa by GPC-RID-20 system ( Fig.2A), which was higher than that (37.6 kDa) of the EPS from B.Amyloliquefaciens 3MS [22]. The molecular weight of the EPS varied with the producing strain, and it might be affected by fermentation time and medium composition [23].…”
Section: Characterization Of Epsmentioning
confidence: 92%
“…Its hydroxyl radical (45.65% at 0.1 mg/mL) and superoxide radical (67.31% at 0.25 mg/mL) scavenging activities were comparable to vitamin C (Table 1). It is noticeable that some EPS not only have antioxidant activity, but also inhibit the growth of cancer cells (Tables 1 and 2) [62,63,132]. For instance, El-Newary et al [62] found an exopolysaccharide (BAEPS) produced by the marine Bacillus amyloliquefaciens 3MS 2017, which contains 22.8% sulfate and has a molecular weight of 37.6 kDa.…”
Section: Bacterial Polysaccharidesmentioning
confidence: 99%
“…It is noticeable that some EPS not only have antioxidant activity, but also inhibit the growth of cancer cells (Tables 1 and 2) [62,63,132]. For instance, El-Newary et al [62] found an exopolysaccharide (BAEPS) produced by the marine Bacillus amyloliquefaciens 3MS 2017, which contains 22.8% sulfate and has a molecular weight of 37.6 kDa. The IC 50 values of BAEPS on radical scavenging of DPPH and hydrogen peroxide were 0.21 and 30.04 µg/mL, respectively.…”
Section: Bacterial Polysaccharidesmentioning
confidence: 99%